Pengaruh Kompensasi dan Kepuasan Kerja Terhadap Kinerja Karyawan pada Perusahaan Perkebunan di Tapanuli Selatan - Muhammad Ras Muis; Atika Aini Nasution (Maslahah : Jurnal Manajemen dan Ekonomi Syariah, 2023)
: The quality of human resources is one of the factors for increasing the productivity and performance of a company. One of the goals of improving the quality of human resources is to ensure that the organization/company has quality people to achieve organizational goals. As one of the main drivers in the smooth running of a company's activities, the important role of human resources requires every company to pay attention to and motivate its employees to provide good performance. The research method used is an associative method with a quantitative approach, which can be interpreted as a research statement that asks about the relationship between two or more variables. The population in this study were 33 employees who worked at the Medan Plantation Company. The data collection technique was carried out using a questionnaire. Based on the results of partial hypothesis testing, the results showed that each compensation and job satisfaction variable had a partial effect on employee performance. The results of the simultaneous testing resulted in an F-count value of 8,472 with a significance level of 0.000, while the f-table value at alpha 5% was 3.32, therefore based on the calculation results it was concluded that F-count > F-table and the significance level was 0.001 < 0.05 shows that compensation and job satisfaction together have a positive and significant influence on employee performance in Plantation Companies. The results of testing the coefficient of determination (R2), obtained an R-Square value of 0.361, this means that 36.1% of the variation in employee performance values ​​is determined by the role of variations in compensation values ​​and job satisfaction so it can be concluded that the contribution of compensation values ​​and job satisfaction in influencing employee performance was 36.1% while 63.9% was the contribution of other variables not included in this research.